Integrating Guided Inquiry Learning, Metacognitive Strategies, and LMS Support to Enhance Academic Writing in Higher Education - Uswatun Hasanah; Rangga Firdaus; Hasan Hariri; Handoko Handoko; Rabiyatul Adawiyah Siregar (Online Learning In Educational Research (OLER), 2026)
Academic writing is a core competency in higher education, yet many university students continue to struggle with constructing coherent arguments, synthesizing evidence, and regulating the writing process. Although Guided Inquiry Learning (GIL), metacognitive strategies, and Learning Management Systems (LMSs) have each demonstrated educational benefits, limited research has examined their integrated use to support academic writing. This study investigated the effectiveness of integrating GIL, metacognitive strategies, and LMS support to enhance students’ academic writing skills. A quasi-experimental pretest–posttest control group design was conducted with 120 sixth-semester undergraduate students from two Indonesian universities. Students’ academic writing performance was assessed before and after the intervention using a standardized writing assessment. The findings showed that both groups had comparable initial writing abilities. After the intervention, students who experienced the integrated instructional approach demonstrated substantially greater improvement in academic writing than those receiving conventional instruction. The integration of inquiry-based learning, metacognitive regulation, and LMS-supported learning promoted more structured writing, reflective learning processes, and stronger academic argumentation. These findings highlight the value of an integrated pedagogical framework for strengthening academic writing instruction in higher education.